(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Menopause is permanent cessation of menstruation at the end of reproductive life due to loss of ovarian follicular activity and hormone deficiency which causes various symptoms and negative effects on life. This study aimed to find out the awareness level of menopausal symptoms and effect on daily life of postmenopausal women. Method: A cross sectional study was conducted during April 2018 to February 2019 to find out the awareness level of menopausal symptoms and effect on daily life among postmenopausal women attending female outpatient department of Patan Hospital, Nepal. Non probability purposive sampling technique was used. Data were collected using structured interview schedule. The SPSS version 16 software was used for data analysis. The association between variables was measured by chi-square test Result: Among 160 postmenopausal women, the overall awareness of menopausal symptoms was inadequate in 130 (81.2%), effect on daily activities in 95 (59.3%), on work efficiency in 94(58.8%) and on social activities in 69 (43.2%). Educational, marital and occupational status were significantly associated with awareness level of menopausal symptoms and the symptoms had significant effect on daily life. Conclusion: The study revealed that more than two third of postmenopausal women had inadequate awareness of menopausal symptoms and more than half had effect on daily life. Educational, marital and occupational status were significantly associated with awareness level.